Răspuns :
x+y=32
y+z=28
z+x=28=>z=28-x
y+z=28==>y+28-x=28==>x=y
x+y=32>>2x=32==>x=16=y>>z=28-x=28-16=12
y+z=28
z+x=28=>z=28-x
y+z=28==>y+28-x=28==>x=y
x+y=32>>2x=32==>x=16=y>>z=28-x=28-16=12
x+y=32
y+z=28
x+z=26
adunand relatiile astea obtii
2(x+y+z)=86
impartind la 2
x+y+z=43
din asta si primele 3 obtii
x=15
y=17
z=11
*s-ar putea sa fi gresit calculele , am facut in graba
y+z=28
x+z=26
adunand relatiile astea obtii
2(x+y+z)=86
impartind la 2
x+y+z=43
din asta si primele 3 obtii
x=15
y=17
z=11
*s-ar putea sa fi gresit calculele , am facut in graba